Interactivity - Hypertextuality - Transversality. A media-philosophical analysis of the Internet - Sandbothe, Mike (HERMES - Journal of Language and Communication in Business, 2000)
My considerations are organized into three parts. In the first part I expand upon the influence of the Internet on our experience of space and time as well as our concept of personal identity. This takes place, on the one hand, in the example of text-based Internet services (IRC, MUDs, MOOs), and through the World Wide Web’s (WWW) graphical user-interface on the other. Interactivity, the constitution characteristic for the Internet, stands at the centre of this. In the second part I will show how the World Wide Web in particular sets in motion those semiotic demarcations customary until now. To this end I recapitulate, first of all, the way in which image, language and writing have been set in rela-tion to one another in the philosophical tradition. The multimedia hypertext-uality which characterizes the World Wide Web is then revealed against this background. In the third, and final, part I interpret the World Wide Web’s hypertextual structure as a mediative form of realization of a contemporary type of reason. This takes place on the basis of the philosophical concept of tranversality developed by the German philosopher Wolfgang Welsch.